Investigating the Reactivity of Single Atom Alloys Using Density Functional Theory - Thirumalai, Hari; Kitchin, John R. (Topics in catalysis, 2018)
Single atom alloys are gaining importance as atom-efficient catalysts which can be extremely selective and active towards the formation of desired products. They possess such desirable characteristics because of the presence of a highly reactive single atom in a less reactive host surface. In this work, we calculated the electronic structure of several representative single atom alloys. We examined single atom alloys of gold, silver and copper doped with single atoms of platinum, palladium, iridium, rhodium and nickel in the context of the d -band model of Hammer and Nørskov. The reactivity of these alloys was probed through the dissociation of water and nitric oxide and the hydrogenation of acetylene to ethylene. We observed that these alloys exhibit a sharp peak in their atom projected d -band density of states, which we hypothesize could be the cause of high surface reactivity. We found that the d -band centers and d -band widths of these systems correlated linearly as with other alloys, but that the energy of adsorption of a hydrogen atom on these surfaces could not be correlated with the d -band center, or the average reactivity of the surface. Finally, the single atom alloys, with the exception of copper–palladium showed good catalytic behavior by activating the reactant molecules more strongly than the bulk atom behavior and showing favorable reaction pathways on the free energy diagrams for the reactions investigated.